A facile approach to prepare crumpled CoTMPyP/electrochemically reduced graphene oxide nanohybrid as an efficient electrocatalyst for hydrogen evolution reaction - Ma, Juanjuan (2017)
Elaborate design and synthesis of efficient and stable non-Pt electrocatalysts for some renewable energy related conversion/storage processes are one of the major goals of sustainable chemistry. Herein, we report a facile method to fabricate Co porphyrin functionalized electrochemically reduced graphene oxide (CoTMPyP/ERGO) thin film by direct assembly of oppositely charged tetrakis(N-methylpyridyl) porphyrinato cobalt (CoTMPyP) and GO nanosheets under mild conditions followed by an electrochemical reduction procedure. STEM analysis confirms that CoTMPyP nanoaggregates are homogeneously distributed over the graphene surface. The electrochemical properties of CoTMPyP/ERGO were investigated by cyclic voltammetry, linear sweep voltammetry and electrochemical impedance spectroscopy. The results demonstrate that CoTMPyP/ERGO nanohybrid film can serve as excellent electrocatalyst for hydrogen evolution in alkaline solution with high activity and stability. The intimate contact and efficient electron transfer between CoTMPyP and ERGO, as well as the crumpled structure, contribute to the improvement of the electrocatalytic performance.